Symbiosis of fire service and volunteer fire brigades in rescue firefighting of today’s world (Academic Journal of Internal Affairs, 2020)
The volunteer fire brigade associations (hereinafter: VFA) are social organizations and independent legal entities, in which the members of the association voluntarily, without payment, undertake their duties in their free time. The precondition for their participation in firefighting, technical rescue and fire prevention tasks is a cooperation agreement concluded with the professional fire brigade of the given area of operation, as proper professional management and supervision are essential for the performance of these tasks. For a long time after the War of Independence in 1848-49, there was no VFA in Hungary, only Count Ödön Széchenyi obtained a change and formed the first full-time firefighting association in 1866 in Sopron and in 1870 in Pest. Over the years the organisation of fire fighting had changed a lot, sometimes the fire departments were controlled by the state sometimes by the local government. The last significant change took place on 1st January 2012, when the professional fire brigades controlled by municipalities came under state control again. A well functioning VFA has always played an important role in carrying out firefighting and technical rescue and local public information tasks. They are also involved in defence and damage prevention tasks (flood and inland water protection, storm damages, red mud disaster) in the managing of catastrophic situations with increasing frequency nowadays. In the last years the number of VFA has also increased significantly, while in 2010 283 in 2019 630 VFA had cooperation agreements. The government also acknowledges the key role of the work carried out by the VFA, so the amount of state support, which has been decreasing on HUF 120 million until 2012 reached with constantly increase an amount HUF 700 million by 2019. Volunteering benefits both individuals and groups, as well as society, and therefore is an important goal to increase the number of volunteers and volunteering activities. That is why 2011 was the European Year of Volunteering, as proposed by the European Commission in June 2009 and decided by the European Council in November 2009. The date of 2011 was symbolic, as ten years had passed since the United Nations declared the Year of International Volunteering in 2001.
Keywords: fire protection; volunteer firefighters; professional firefighters; collaborations